THU0267 SERUM IGG2 LEVELS PREDICT VERY LONG-TERM PROTECTION FOLLOWING PNEUMOCOCCAL VACCINE IN SYSTEMIC LUPUS ERYTHEMATOSUS (SLE). (13th June 2020) - Goulenok, T.; Gerard, A. L.; Bahuaud, M.; Aucouturier, P.; Moins, H.; Papo, T.; Sacre, K.
Abstract : Background: Systemic lupus erythematosus (SLE) patients are at increased risk for Streptococcus pneumoniae infection. Although pneumococcal vaccination is an attractive method to prevent invasive pneumococcal infection, vaccination coverage remains dramatically low in SLE. Moreover, the efficacy of vaccination may be reduced in SLE patients and sequential pneumococcal vaccination using new conjugated pneumococcal vaccines in combination with 23-valent pneumococcal polysaccharide vaccine (PPV23) is now advocated. However, limited study directly addressed the immune efficacy of such prime-and-boost strategy in SLE Objectives: We aimed to measure the immunological efficacy of the sequential pneumococcal vaccination using PCV13 in combination with PPV23 and identify factors associated with long-term immune protection following vaccination in SLE. Methods: SLE patients received PCV13 vaccine followed by PPSV23 vaccine 8 weeks later. Immune protection, defined by an antigen-specific IgG concentration ≥ 1.3 µg/mL for at least 70% of 7 pneumococcal serotypes (4, 6B, 9V, 14, 18C, 19F, 23F), was assessed at baseline, 2 months, 12 months, and 36 months, defining very long-term protection. Results: 21 (40[25-75] years; 85.7% female) SLE patients received the sequential PCV13/PPV23 vaccines. Only 10 (47.6%) showed a sustained immune protection against pneumococcal infection 36 months after PCV13 shot (very long-term protected, VLTP). Eleven patients had no long-term protection (NLTP) with a seroconversion that never (n=6) or only transiently (n=5) occurred. SLE disease features, treatment received and immunological characteristic did not differ between VLTP and NLTP patients except for a lower serum IgG2 levels in NLTP (1.45 [1.30, 1.82] vs 3.30 [2.92, 4.44] g/L, p<0.001). Noteworthy the ROC curve showed that the serum IgG2 level before vaccination (AUC 0.95 [95% CI: 0.84-1]; p=0.004) was predictive for very long-term protection. A baseline serum IgG2 level of 2.125µg/ml or more showed a sensitivity of 100% and a specificity of 90.9% for very long-term protection Conclusion: The benefit of sequential PCV13/PPV23 vaccination in SLE is limited. Baseline IgG2 serum level before vaccination is strongly indicative of very long term protection following vaccination Disclosure of Interests: None declared